LncRNA LUCAT1 as a Plasma Biomarker for Assessing Disease Activity in Adult Patients with Crohn’s Disease - Xiao-yi Kuai; Shun-ying Yu; Xiu-fang Cui; Xiao-jing Zhao; Xia-qiong Mao; Yang Yu; Tong Hu; Hong-jie Zhang; Chun-li Zhou (Gastroenterology Research and Practice)
Aim. To explore the expression of long noncoding RNA (LncRNA) LUCAT1 in adult patients with Crohn’s disease (CD) and evaluate the relationship between LncRNA LUCAT1 and the disease activity in Chinese patients with CD. Methods. Patients with CD and healthy participants (≥18 years old) were enrolled in this study between January 2018 and December 2019. The expression of LncRNA LUCAT1 in plasma samples was evaluated by quantitative reverse transcription-polymerase chain reaction. Basic characteristics of patients with CD were collected, including gender, age, clinical stage, disease behavior, disease location, C-reactive protein (CRP), platelet (PLT), erythrocyte sedimentation rate (ESR), fecal calprotectin (FC), Crohn’s disease activity index (CDAI) score, and simplified Crohn’s disease endoscopic score (SES-CD). Results. In total, 168 patients with CD and 65 healthy participants (≥18 years old) were enrolled in this study. Among them, ninety patients with clinically active CD, seventy-eight patients with CD in clinical remission, forty-eight patients with endoscopically active CD, thirty patients with endoscopically inactive CD, and sixty-five healthy participants. LncRNA LUCAT1 was increased in plasma of patients with CD compared with the control group. The plasma LncRNA LUCAT1 level of patients with CD both in the clinical and endoscopic active phase was higher than that of both the clinical and endoscopic remission phase. The plasma level of LncRNA LUCAT1 in patients with CD was positively correlated with ESR, CRP, FC, CDAI, and SES-CD. There was no significant correlation between the level of LUCAT1 and platelets. The plasma LncRNA LUCAT1 level in patients with CD had significant differences between severe active patients and mild/moderate active patients. Conclusion. The plasma LncRNA LUCAT1 is positively associated with the disease activity in patients with CD, and it may act as a noninvasive biomarker to identify the degree of disease activity.